2017
DOI: 10.1177/0361684317690119
|View full text |Cite
|
Sign up to set email alerts
|

Secondary and 2-Year Outcomes of a Sexual Assault Resistance Program for University Women

Abstract: We report the secondary outcomes and longevity of efficacy from a randomized controlled trial that evaluated a novel sexual assault resistance program designed for first-year women university students. Participants (N = 893) were randomly assigned to receive the Enhanced Assess, Acknowledge, Act (EAAA) program or a selection of brochures (control). Perception of personal risk, self-defense self-efficacy, and rape myth acceptance was assessed at baseline; 1-week postintervention; and 6-, 12-, 18-, and 24-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 69 publications
2
121
0
1
Order By: Relevance
“…Of particular interest is that women correctly identified relatively weaker male vocalizers on only 25% of trials, and tended to judge similar strength male vocalizers as stronger than themselves. Awareness of this negative bias may inform confidence-based interventions (already shown to ameliorate the “confidence gap” in cognitive tasks, Bench et al., 2015 , Ehrlinger and Dunning, 2003 , Estes and Felker, 2012 ) in sexual assault resistance programs ( Jordan and Mossman, 2017 , Senn et al., 2015 , Senn et al., 2017 , Wong and Balemba, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is that women correctly identified relatively weaker male vocalizers on only 25% of trials, and tended to judge similar strength male vocalizers as stronger than themselves. Awareness of this negative bias may inform confidence-based interventions (already shown to ameliorate the “confidence gap” in cognitive tasks, Bench et al., 2015 , Ehrlinger and Dunning, 2003 , Estes and Felker, 2012 ) in sexual assault resistance programs ( Jordan and Mossman, 2017 , Senn et al., 2015 , Senn et al., 2017 , Wong and Balemba, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in Canada, Kenya, and the U.S. has found that women are much less likely to be assaulted after taking an empowerment‐based self‐defense class (Hollander, ; Sarnquist et al, ; Senn et al, ; Sinclair et al, ). These effects are both large and immediate and, according to one study, are sustained over at least 2 years (Senn et al, ). In addition, participants in these studies report a range of other positive effects.…”
Section: Women's Self‐defense and Sexual Assault Resistance: The Statmentioning
confidence: 98%
“…They are also evidence‐based, provide a comprehensive “toolbox” of strategies for the full continuum of assaults against women, explicitly hold perpetrators responsible for violence, transform understandings of women's bodies and gender more generally, and aim to empower rather than frighten or restrict women (National Women's Martial Arts Federation, n.d.; Hollander, ; ; Hollander, In press; Rentschler, ; Searles & Follansbee, ; Seith & Kelly, ; Taylor & Wanamaker, ; Telsey, ; Thompson, ; Wanamaker, ). ESD courses thus go far beyond the physical training that most people associate with the term “self‐defense.” Although research on ESD training is fairly new, we now have a growing body of rigorously conducted work that demonstrates its effectiveness (Hollander, ; Sarnquist et al, ; Senn et al, ; Senn et al, ; Sinclair et al, ). Nonetheless, there continues to be misunderstanding about both what women's self‐defense is and the differences among the various types of self‐defense training; this confusion has kept ESD classes from becoming an integral part of the antiviolence movement (Thompson, ).…”
Section: What Is Women's Self‐defense?mentioning
confidence: 99%
“…Fund and implement sexual harassment and assault resistance training for students as part of an integrated sexual violence prevention strategy based on the best available evidence 5. Evidence-based programmes exist to help students become more active bystanders39 and better resist sexual violence,40 41 as well as programmes that show promise for reducing male students’ perpetration of sexual violence 42. If ‘ the female researcher cannot prepare for all eventualities, … at least she can enter the setting with some idea of how she might respond to sexist remarks, sexist behavior, and sexual hustling.…”
Section: What Can Academics and Academic Institutions Do?mentioning
confidence: 99%